Clinical and immunologic features of pediatric patients with common variable immunodeficiency and respiratory complications - (:unkn) unknown (ESMON PUBLICIDAD S A, DEPT ALLERGY & CLIN IMMUNOL, CLIN UNIV NAVARRA, 2008)
Background: Common variable immunodeficiency (CVID) is the term used to describe a heterogeneous group of B-cell deficiency syndromes characterized by hypogammaglobulinemia, impaired antibody production, and recurrent bacterial infections. Objectives: To determine the clinical manifestations and perform an immunological analysis of pediatric CVID patients suffering from respiratory complications. Methods:The records of 10 patients with CVID who were followed up from 1992 to 2005 (6 males and 4 females) with a median (interquartile range) age of 13.9 (10.4-19.4) years were reviewed. All patients met the standard criteria set for CVID. Results: Median total serum levels of immunoglobulin (Ig) G, IgM, and IgA in mg/dL were 383.5 (239.2-574.5), 32.5 (17.0-117.0), and 12.5 (5.0-30.7), respectively. Median age at the onset of symptoms, at CVID diagnosis, and on starting intravenous Ig therapy was 4.0 (0.86.2), 9.4 (6.7-11.3), and 9.1 (7.0-11.6) years, respectively. Associated disorders were recurrent infections (100%), bronchiectasis (90%), and growth failure (80%), whereas malabsorption, malignant neoplasm, inflammatory bowel disease, and autoimmune disorders were less common. All bronchiectatic patients had a low percentage of B cells, with an average of 4% (range, 1%-7%). The characteristic computed tomography finding in patients with CVID was a multilobar pattern. Malignant neoplasm developed an average of 11.5 (range, 6.5-20.2) years after the diagnosis of CVID was made. Conclusion: Recurrent respiratory infection should be evaluated to rule out CVID. Early diagnosis and intravenous Ig replacement therapy may reduce the frequency of respiratory infection. Low levels of serum Ig and percentage of B lymphocytes at diagnosis are important parameters for identifying patients at risk of structural lung damage.
Keywords: bronchiectasis; CVID; pediatric; primary immune deficiency; HYPOGAMMAGLOBULINEMIA; IMMUNOGLOBULIN; DEFICIENCY; DISORDERS; DISEASE